2023
DOI: 10.1007/s00217-023-04215-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Turkish pine honey according to their geographical origin based on physicochemical parameters and chemometrics

Abstract: This study was conducted to determine the characteristic properties of Turkish pine honey, which is an important honeydew honey. The geographical classification of the honey was determined by applying carbon isotope, melissopalynological, and physicochemical analyses to 373 samples collected from 47 regions between 2015 and 2017 under controlled conditions. δ13C protein-δ13Choney, C4%, electrical conductivity, moisture, ash, free acidity, color CIEL* a*b attributes, optical rotation [α]20, proline, diastases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The market for natural honey production in China has experienced some fluctuations over the years but reports released by Access Asia in 2021 revealed that production will continue to rise with rising demand for the product. Although, the country experienced a decline in production levels between 1998 and 1999 and some other periods due to bee diseases and unfavorable weather, it remained the world's leading producer of natural honey [142]. However, China's import of honey has been instigated by the demand from the Food Manufacturing industry, for a specific type of honey not produced in China.…”
Section: Chinamentioning
confidence: 99%
“…The market for natural honey production in China has experienced some fluctuations over the years but reports released by Access Asia in 2021 revealed that production will continue to rise with rising demand for the product. Although, the country experienced a decline in production levels between 1998 and 1999 and some other periods due to bee diseases and unfavorable weather, it remained the world's leading producer of natural honey [142]. However, China's import of honey has been instigated by the demand from the Food Manufacturing industry, for a specific type of honey not produced in China.…”
Section: Chinamentioning
confidence: 99%